2013
DOI: 10.1186/1743-422x-10-15
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in respiratory adenovirus serotypes circulating in the greater Toronto area, Ontario, during December 2008 to April 2010

Abstract: BackgroundCertain adenovirus serotypes cause severe infections, especially in children. It is important to monitor temporal changes in serotypes causing clinical disease. The objective of this study was to document circulating respiratory adenovirus serotypes by sequencing adenovirus culture isolates from the Greater Toronto Area, Ontario, during December 2008 to April 2010.MethodsNucleic acid extraction was performed on 90 respiratory tract adenovirus culture isolates. PCR amplification was conducted with pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 15 publications
(37 reference statements)
2
24
0
Order By: Relevance
“…We reported the prevalence of multiple HAdV types (HAdV-B, HAdV-C, HAdV-D HAdV-E) in paediatric patients with SARI in China from 2007 to 2010 (overlapping the H1N1 pandemic period). Consistent with previous reports [6,[11][12][13][14][15], the HAdV-B and HAdV-C were the most common serotypes for ARI, and co-infection with other respiratory viruses was frequent (64 from 76, especially co-infection with RSV, HRV, HBoV and PIV3). And 32 from 76 were co-infected by two or more viruses.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We reported the prevalence of multiple HAdV types (HAdV-B, HAdV-C, HAdV-D HAdV-E) in paediatric patients with SARI in China from 2007 to 2010 (overlapping the H1N1 pandemic period). Consistent with previous reports [6,[11][12][13][14][15], the HAdV-B and HAdV-C were the most common serotypes for ARI, and co-infection with other respiratory viruses was frequent (64 from 76, especially co-infection with RSV, HRV, HBoV and PIV3). And 32 from 76 were co-infected by two or more viruses.…”
Section: Discussionsupporting
confidence: 91%
“…HAdV-E 1 (4.2) The severity of infection associated with HAdV varies depending on the different HAdV types [10,15]. In addition, the prevalence of different HAdV serotypes varies among different geographical regions [12][13][14][15]. Our study indicated that HAdV was frequently detected in SARI children from 2008 to 2010 (52/259, 20.1%) in Northern China; this frequency was higher than that of cases in Eastern China (24/293, 8.2%) and in other studies [10][11][12]19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More rarely, HAdV infections may lead to haemorrhagic cystitis [4,5]. Severe disease in immunodeficient patients, children and elderly has also been documented [6][7][8]. Infections with adenovirus may occur sporadically or in epidemics and can be detected throughout the year.…”
Section: Introductionmentioning
confidence: 99%